Asian economic integration and maritime CO2 emissions. (March 2016) - Lee, Tsung-Chen; Lam, Jasmine Siu Lee; Lee, Paul Tae-Woo
Highlights: We explore key driving factors through which freer trade affects maritime CO2 emissions. Depending on the level of Asian integration, global CO2 emissions may fall or rise. Higher increase in the maritime CO2 emissions occurs in developing Asian countries. Abstract: The Asian region is considered as the most thriving region in terms of economic integration at present. Given the fact that most of the Asian countries' commodity trade relies on maritime transport, its economic integration is expected to affect the shipping activities and consequently maritime CO2 emissions. This study develops a novel and systematic analysis on the key driving factors through which trade liberalization can influence maritime CO2 emissions. Our simulation results suggest that, depending on the level of Asian integration, global CO2 emissions may slightly fall (ASEAN+3 FTA) or even rise (ASEAN+6 FTA). The reason for the latter is that the "trade scale effect" (higher emissions due to a significant increase in trade among participating countries) outweighs the "trade structure effect" and "shipment type effect" (lower emissions as a result of an increase in intra-Asia trade and a change in commodity composition). Finally, all countries involved in the Asian integration, except Japan, will experience an increase in maritime CO2 emissions. In particular, a relatively significant increase in the maritime CO2 emissions occurs in the developing Asian countries owing to substantial trade scale effect after removing their relatively high trade barriers.